In Limited Demand: The Other Foreign Volunteers in the Syrian Civil War - Mendelsohn, Barak (Terrorism and political violence, 2022)
The wars in Syria and Iraq attracted about 45,000 individuals from outside the arenas. Most joined the Islamic State, but interestingly, other prominent armed groups showed less interest in foreign volunteers. This paper introduces the Demand for Foreign Volunteers Theory (DFVT) to explain the diverging choices Jabhat al-Nusra, Ahrar al-Sham, and the People’s Protection Units made. The theory links four variables that shape groups’ positions: political considerations, operational needs, organizational capacity, and ideational fit. Both operational and political considerations emphasize the motivation for using foreign volunteers, though the two are not equally important; when they conflict, political considerations take priority. Organizational capacity, on the other hand, determines a group’s ability to translate need into action, serving as a necessary—but insufficient—condition for foreign mobilization. Finally, ideational factors, specifically a group’s identity and ideology, determine the pool of potential recruits. The case studies show that political considerations made all three actors cautious about recruiting foreign fighters, though these considerations differed between groups. Ultimately, despite the availability of sufficient organizational capacity, all groups found it risky and even undesirable.